HUBUNGAN SEBARAN MAMALIA KECIL DENGAN KONDISI LINGKUNGAN DI HULU DAS CITANDUY, JAWA BARAT - Maharadatunkamsi, Maharadatunkamsi (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Citanduy watershed is one of major watersheds in Java that located through north to south covering four regencies, these are: Ciamis, Tasikmalaya, Garut and Cilacap. As a consequences of environmental changes, this watershed that covering an are about 473.967 ha has faced in deterioration on its roles. This research was aimed to study on the distribution of small mammals at the upper of Citanduy watershed according to their habitat and altitudinal changes. Results indicated that 20 species of small mammals clustered in three groups of habitat. Group 1 consisted of small mammals that occupied the habitat of mixed pines-calliandra. Group 2 comprised of small mammals lived at secondary forest, bambu plantation, and mixed secondary forest-bamboo; and group 3 were mainly occupied shrub. In addtion, an altitude was also affected the distribution of small mammals in the area surveyed. The results of this study are to be used as a basic information that describe the quality of upper Citanduy watershed.